Comparison of Integrative Lighting Scenarios: Insights from an Office Field Study - Kaplan, Elif; Ozturk, Leyla Dokuzer (TAYLOR & FRANCIS INC, 2026)
Light exerts hormonal, circadian, and behavioral influences beyond its visual function, yet consensus is lacking on the optimal illuminance and correlated color temperature (CCT) for various workplace tasks within the scope of integrative lighting. This study investigates and compares five lighting scenarios-one dynamic and four static-in a real office environment to explore the balance between visual comfort, biological effectiveness, and user preference. The static scenarios comprised horizontal desk-plane illuminance and CCT settings of 500 lx at 4000 K, 1000 lx at 5500 K, 1250 lx at 4000 K, and 1500 lx at 5500 K, while the dynamic scenario varied between 500-1000 lx and 3500-5500 K at the desk plane over the day. Lighting conditions were assessed through objective measurements, melanopic equivalent daylight illuminance calculations, and subjective surveys over short- and long-term exposures. The study found that high illuminance and cool light enhanced alertness and energy, but participants preferred neutral light with elevated illuminance. The scenario with 1250 lx at 4000 K was most favored, providing an optimal balance between visual and nonvisual effects. These findings guide integrative lighting design to enhance office comfort, well-being, and productivity.
Keywords: Dynamic lighting; integrative lighting; melanopic illuminance; office lighting; static lighting; CORRELATED COLOR TEMPERATURE; MELATONIN SUPPRESSION; ACTION SPECTRUM; GANGLION-CELLS; BRIGHT LIGHT; WHITE-LIGHT; SLEEP; EXPOSURE; MOOD; ILLUMINATION; Construction & Building Technology; Optics